Factorial Design Screening For the Red Pigment Production By Monascus Purpureus FTC 535 - Farhan, Mohd Said; Nor Farhana, Hamid (Penerbit UTM Press, 2016)
Factorial design experiment was used to obtain maximum information from the least amount of experimental runs. The goal of this study was to screen the significant factors from multivariable parameters which can influence the production of red pigment by Monascus purpureus FTC 5356 under solid state fermentation (SSF) using oil palm frond (OPF). Five factors such as initial moisture content (A), nitrogen source concentration (B), percentage of OPF leaflet to petiole (C), initial pH of substrate (D), and inoculum size (E) were screened in sixteen experimental runs. To reduce cost, the feasibility of OPF as an alternative substrate was investigated. Percentage of OPF leaflet and initial pH of OPF substrate contributed significantly (P-values of 0.0121 and 0.0229, respectively). Meanwhile, other factors such as initial moisture content (P- value 0.0766) and inoculum size (P-value 0.0895) had least impact to the red pigment production.